Interventions to improve the quality of maternal care in Ethiopia: a scoping review - Birhane, Binyam Minuye; Assefa, Yibeltal; Belay, Demeke Mesfin; Nibret, Gedefaye; Munye Aytenew, Tigabu; Liyeh, Tewachew Muche; Gelaw, Kelemu Abebe; Tiruneh, Yenework Mulu (Frontiers in Global Women's Health, 2024)
Introduction Quality improvement interventions have been part of the national agenda to avert maternal and neonatal morbidities and mortality. Despite different interventions, neonatal mortality and morbidity rates remain steady. This review maps and synthesizes the evidence of maternal and newborn quality improvement interventions in Ethiopia. Methods A scoping review was reported based on the reporting items for systematic reviews and meta-analysis extensions for the scoping review checklist. Data extraction, collating, and organization were based on the Joanna Briggs Institute manual of the evidence synthesis framework for a scoping review. The World Health Organization’s maternal and neonatal care standards and Donabedian’s model quality of health framework were used to summarize the findings. Result Nineteen articles were included in this scoping review. The review found that the studies were conducted across various regions of Ethiopia, with the majority published after 2013. The reviewed studies mainly focused on three maternal care quality interventions: mobile and electronic health (eHealth), quality improvement standards, and human resource mobilization. Moreover, the review studies explore various approaches to quality improvement, such as training (health care workers, health extension workers, traditional birth attendants, the community health development army, and mothers) and supply resources needed for maternal and newborn care. Conclusion In conclusion, quality improvement strategies encompass community involvement, health education, mHealth, data-driven approaches, and strengthening the health system. Future research should focus on the impact of the physical environment, culture, sustainability, cost-effectiveness, and the long-term effects of interventions. Healthcare providers' knowledge, skills, attitudes, satisfaction, and adherence to the guidelines should also be considered.